Fighter Planes: Fearless Fliers - Bledsoe, Karen E.; Bledsoe, Glen. (Berkeley Heights, NJ : Enslow Publishers, 2006)
Facts about high-tech fighter jets, from today's F-15 Eagles to tomorrow's F/A-22 Raptors.
Surprise mission -- Fighter planes to fighter jets -- F-15 Eagle -- F-16 Fighting Falcon -- F/A-18 Hornet -- Training to be a fighter pilot.
Includes bibliographical references (p. 47) and index.
Keywords: Eagle (Jet fighter plane); F-16 (Jet fighter plane); Hornet (Jet fighter plane); Air pilots -- Training; Fighter planes